Granulomatosis with polyangiitis as a differential diagnosisin intensive care unit: a case report - Araujo Neurauter, Anna Luiza; Abreu Lima, Karen; Domingos Almeida, Maitê; Marins Feres, Rodrigo; Freitas Teixeira, Mateus; Andrade Albán, Noemí (Mediciencias UTA, 2018)
Granulomatosis with polyangiitis, a small vessels vasculitis, involves mostly upper respira-tory tract, lungs and kidneys. It’s a multisystemic pathology, with no sex predominance, affecting adults over 40 years old. Case report: K.S.D, 64 years, female, came to emergency room with dyspnea, cough and coryza, 15 days after a recurrent acute otitis media surgical treatment. A CT showed bilateral pleural effusion, consolidation and a lung mass, being admitted in Intensive Care Unit. Subsequently, developed mastoiditis and conjunctival hyperemia and used several antibiotic therapys. Patient was discharged 40 days later, with clinical improvement. One month later, was admitted again with pulmonary septic shock, in addition to sinusitis, polyarthralgia, purpura and acute renal injury, requiring hemodyalisis. Biomarkers were requested, such as c-ANCA and rheumatoid factor, with positive result and antinuclear factor, with negative result. A renal biopsy also has been solicitated, showing glomerulonephritis. The diagnosis was granulomatosis with polyangiitis, treated with meth-ylprednisone pulse therapy and cyclophosphamide, progressing to clinical stability and receiving discharge with outpatient follow-up. Conclusion: Granulomatosis with polyangiitis is a rare condi-tion, with that should be considered when patient presents the triad: upper and lower airways and glomerulonephritis. Early diagnosis and immunosuppressive therapy are essential to reduce its morbimortality.